2017
DOI: 10.11138/orl/2017.10.3.270
|View full text |Cite
|
Sign up to set email alerts
|

The Flap Recovery on the Impacted Lower Third Molar Surgery Comparing 3 Different Flap Designs: A Clinical Study

Abstract: SUMMARYAim. The purpose of the study was to analyze the healing of the deep and superficial lower first and second molars periodontium, after the surgical extraction of the contiguous impacted third molar, comparing 3 mucoperiosteal flap designs. Materials and methods. 150 patients which had to undergo a impacted lower third molar surgery were enrolled in this study. They were checked from day 0 to day 90, in order to focus on the recovery quality of the soft tissues around the lower second molar, comparing 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…One study reported a significant increase in gingival recession at the disto-vestibular site of the second molar after surgery. The other study observed only two small recessions among the 150 patients included [47].…”
Section: Gingival Recessionmentioning
confidence: 83%
See 2 more Smart Citations
“…One study reported a significant increase in gingival recession at the disto-vestibular site of the second molar after surgery. The other study observed only two small recessions among the 150 patients included [47].…”
Section: Gingival Recessionmentioning
confidence: 83%
“…Gingival recession was assessed in two studies [32,47]. One study reported a significant increase in gingival recession at the disto-vestibular site of the second molar after surgery.…”
Section: Gingival Recessionmentioning
confidence: 99%
See 1 more Smart Citation
“…To go into discussion, it is known that patients younger than 30 years of age have better full recovery of their M3 injury [23,24] and the risk of complications and postoperative morbidity [22], as well as the incidence of transitory lip sensitivity [25], in patients younger than 25 years old are reported to be lower compared with older patients. Therefore, our data agree well with many studies reporting the age of 25 years as a critical time, after which complications increase more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods over recent years have been suggested and utilized to minimize post-operative sequelae, such as platelet-rich fibrin administration ( Gülşen and Şentürk, 2017 ), laser application ( Kahraman et al, 2017 ), cryotherapy ( Zandi et al, 2016 ), drug injections ( Gorecki et al, 2017 ), and various flap designs ( Ottria et al, 2017 ). However, one of the most important methods has involved the use of osteotomy techniques to minimize trauma and the generation of heat associated with cutting the bone or osteotomy during surgical extraction of the lower third molars ( Al-Delayme, 2013 ).…”
Section: Introductionmentioning
confidence: 99%